A lovable personality: The effect of brand personality on brand love. Issue 5 (September 2016) - Roy, Pinaki; Khandeparkar, Kapil; Motiani, Manoj
Abstract This study proposes and empirically tests the impact of two dimensions of brand personality (excitement and sincerity) on brand love and, subsequently, on store brand loyalty and +WOM in the context of online retailers. The data were collected from 500 respondents to test the proposed model using structural equation modeling (SEM). The results demonstrated that the two dimensions of brand personality as well as brand love have a positive impact on store brand loyalty and +WOM. Additionally, 'sincerity' and 'excitement' had a direct effect on store brand loyalty but not on +WOM. However, both the personality dimensions influenced +WOM through brand love and store brand loyalty.